2010
DOI: 10.1074/jbc.m109.077453
|View full text |Cite
|
Sign up to set email alerts
|

Serine- and Arginine-rich Proteins 55 and 75 (SRp55 and SRp75) Induce Production of HIV-1 vpr mRNA by Inhibiting the 5′-Splice Site of Exon 3

Abstract: HIV-1 non-coding exon 3 can either be spliced to exons 4, 4a, 4b, 4c, and 5 to generate tat, rev, and nef mRNAs or remain unspliced to produce the 13a7 vpr mRNA. Here we show that serine-and arginine-rich proteins 55 and 75 (SRp55 and SRp75) inhibit splicing from the 5-splice site of exon 3 thereby causing an accumulation of the partially unspliced 13a7 vpr mRNA. In contrast, serineand arginine-rich protein 40 (SRp40) induces splicing from exon 3 to exon 4, thereby promoting the production of the 1347 tat mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…As all SR proteins, it can either activate or inhibit splicing. A recent study demonstrated that SRp75 inhibits use of a 5′ splice site in HIV-1 RNA but the details of its action were not determined (Tranell et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…As all SR proteins, it can either activate or inhibit splicing. A recent study demonstrated that SRp75 inhibits use of a 5′ splice site in HIV-1 RNA but the details of its action were not determined (Tranell et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…13 While SR proteins typically enhance splicing, SRSF6 has demonstrated negative regulation of a 5′-splice site and can act antagonistically to another SR protein. 14,15 For antagonistic actions between splicing regulators, local concentrations of the respective proteins are critical for proper splice site usage. 15 Given that SRSF6 can both negatively regulate splicing and can potentially interact with U1 snRNP, there are two possible mechanisms by which it can influence huntingtin splicing: a large SRSF accumulation near the 5′-splice site may inhibit splicing of intron 1 or SRSF6 binding to the expanded CAG repeat may sequester the local U1 snRNP.…”
Section: Huntingtin Exon 1-intron 1 Junctionmentioning
confidence: 99%
“…Mutants compared with full-length ZNF638: * P < 0.05, ** P < 0.01. This model is supported by the identifi cation through our mass spectrometry analysis of SRSF4, a splicing factor previously shown to be involved in alternative splice site selection during pre-mRNA processing ( 44,45 ), as a novel ZNF638 interactor. This putative dual function of ZNF638 is reminiscent of the splicing role played by the coactivator PGC1 ␣ when loaded on the promoter of its target genes ( 23 ).…”
Section: Znf638 Modulates Alternative Splicing Decisions On a Minigenmentioning
confidence: 52%